The Hierarchy of Needs Analysis on Brianna Jackson in On the Come Up Novel by Angie Thomas - Alaydrus, Syarifah Fairuz Shafira; Valiantien, Nita Maya; M, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This research discusses the needs of a character named Brianna Jackson in On the Come Up novel by Angie Thomas. The theory applied for the study is the hierarchy of needs theory proposed by Maslow and characterization theory by Kenan. Under the umbrella of qualitative research, this study uses the psychological criticism approach to find out whether Brianna is able to fulfill all her needs and her character portrayal based on how she fulfills her needs. Living as a struggling sixteen year-old girl always challenges Brianna to attain even her most basic needs. The analysis reveals that Brianna manages to satisfy her physiological need, safety need, love and belongingness need, and esteem need. However, her self-actualization need is failed to be fulfilled due to some of Brianna’s actions being unfit as a self-actualizing person. Out of fifteen required characteristics in self-actualization, there are only five of them that are found in Brianna. The other eight characteristics were unfulfilled since they contradicted with Brianna’s behavior. Meanwhile, the other two were not reflected. Nonetheless, the exploration of her actions in fulfilling her needs also unveils the way Brianna’s character is portrayed in the novel. It turns out that Brianna is an argumentative, impulsive, confident, and determined character who always tries her best in securing her needs no matter how hard things get for her.